Efficacy of fermented cassava pulp with chicken manure on nutrients digestibility, haematological parameters, and growth performance of barrow pigs - Simon Anthony Kayombo; Pattaraporn Poommarin; Panida Duangkaew (Northern Negros State College of Science and Technology (NONESCOST), 2022)
Cassava pulp is a by-product from the starch industry which was used as cheap alternative livestock feed. However, it has a limitation of low protein and high fibre to use in monogastric animals. Nutrient improvement of cassava pulp usually employs the use of inorganic nitrogen fertilizer. Here we demonstrated the use of chicken manure as an organic nitrogen source in compensation for the inorganic nitrogen. This research aimed to investigate the efficacy of cassava pulp fermented by dried chicken manure with yeast (CPCM) in a maize-soybean-based diets of pigs on nutrients digestibility, haematological parameters, and growth performance of barrow pigs as alternative energy feed. The results showed that the CPCM had crude protein increase from 1.99% of the plain cassava pulp to 8.54% (p < 0.05), while the crude fibre of CPCM decreased from 15.63 to 13.85%. Investigation of the diets containing CPCM as a replacement of maize at 4 levels (0%, 5%, 10%, and 15%) in twenty-four castrated male pigs (57.13 ± 3.29 kgs initial bodyweight) revealed that the control diet (0%CPCM) had the greatest digestibility percentages in all categories including dry matter, crude protein, crude fibre, gross energy, and total phosphorus (p < 0.05). Among CPCM replacement diets, the 15%CPCM generally verified a greater digestibility. The results of the feeding trial showed that there was no significant difference (p > 0.05) in feed intake, weight gain, feed conversion ratio, and haematological parameters among the four treatment diets. The haematological results showed that all parameters fall under the normal ranges of haematological pigs' references. In conclusion, the results confirmed that CPCM can be used in the replacement of up to 15% in maize-soybean pig diets without any harmful effects.